QBD-DRIVEN STABILITY INDICATING RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF NINTEDANIB ESYLATE - SAWANT, SANJAY DINKAR; TANGDE, JYOTI BHAGWAN (International Journal of Applied Pharmaceutics, 2025)
Objective: The present research work focuses on evaluation of Nintedanib esylate (NTB) with development and validation of Reverse Phase High-Performance Liquid Chromatography (RP-HPLC) method pertaining to quality by design-based force degradation study. Methods: A two-level, two-factorial design has been used with predetermined design specifications using design expert software. The RP-HPLC method was developed with isocratic mode using a C-18 column at a 392 nm detection wavelength. Results: The calibration curve was found to be linear with R² = 0.9996. Retention Time (RT) was obtained at 6.14; Limit of Detection (LOD) and Limit of Quantitation (LOQ) were found to be 1.4121 μg/ml and 4.2790 μg/ml, respectively. Relative Standard Deviation (RSD) for intraday precision was 1.799% and for interday precision 1.563%, respectively. Degradation studies found out the drug is susceptible to acidic, oxidative, and photolytic conditions, while the drug was found to be stable in thermal and alkaline conditions. Conclusion: The resulting method holds potential for application in routine analysis of nintedanib esylate in capsule formulation in compliance with International Council for Harmonization (ICH) guidelines.